Ease and practicability of the 2017 classification of periodontal diseases and conditions: a study of dental electronic health records - Muhammad Raza; Daniela Gurpegui Abud; Joseph Wang; Jaffer Ahmed Shariff (BMC, 2024)
Abstract Background A new classification for Periodontal and Peri-implant Diseases and Conditions was introduced in the 2017 World Workshop. In the past the 1999 Armitage Classification was commonly used in practice. This study aimed to assess the ease and practicability of retroactively diagnosing a subset of patients formerly diagnosed using the 1999 AAP/CDC classification with the 2017 AAP/EFP disease classification. Methods A random subset of 10% of all patients referred over a 7-year period (2011-2018) to the Post-Doctoral Periodontics Clinic at Columbia University College of Dental Medicine were reviewed by accessing the Electronic Health Records (EHRs) on axiUm. Patients diagnosed with periodontal disease based on the 1999 AAP/CDC classification (including chronic and aggressive Periodontitis) were reclassified using the 2017 classification (stage: I, II, III and grade: A, B, C). Results A sample of 336 patient records were examined. 132 were diagnosed with gingivitis, and 204 with periodontitis. Of these 204 patients, 68 (33.3%) were diagnosed with aggressive and 136 (66.7%) with chronic periodontitis. Patients diagnosed with aggressive periodontitis, 10% were reclassified as stage II, 47% as stage III, and 43% as stage IV periodontitis, and 100% were reclassified as grade C. Among patients with chronic periodontitis, 7% were reclassified as stage I, 65% as stage II, 21% as stage III, and 7% as stage IV; 11% of these were reclassified as grade A, 63% grade B, and 26% grade C. Conclusions The majority of those originally diagnosed with aggressive (90%) and chronic (80%) periodontitis were reclassified as either molar/incisor pattern stage III grade C or stage IV grade C periodontitis, and stage II or III periodontitis, respectively. The study demonstrated that it is practical to retroactively reassign a diagnosis according to the new 2017 classification using available information included in dental EHRs.